What’s in a flash?: Teaching reading and writing (and beyond) through flash fiction - Veronico N. Tarrayo (Universitas Islam Malang, 2019)
Literature teaching (and the teaching of reading, in general) is challenged by many rivals with which it competes for the attention and interest of the younger generation called the ‘digital natives.’ This article introduces flash fiction as one possible way to regain the interest of the young to journey and explore the interesting world of literature. Flash fiction as bite-sized stories may be a less intimidating yet challenging (because it requires rich language) venue for learners to develop their creative reading and writing skills.This article begins with a concise discussion on the problem of reading among young people nowadays, and then proceeds with an introduction of flash fiction as a literary genre. Most importantly, the paper discusses the place of flash fiction in the academe and offers practical knowledge on the use of the said literary genre in the teaching of reading and writing.